An Explicit Method for the Split Feasibility Problem with Self-Adaptive Step Sizes - Youli Yu (Abstract and Applied Analysis)
An explicit iterative method with self-adaptive step-sizes for solving the split feasibility problem is presented. Strong convergence theorem is provided.